72 seasons [compact disc] (Blackened Recordings, 2023)
Towards the end of 2022, Metallica surprised the music world by announcing the release of their twelfth studio album, as well as releasing the new single Lux Aeterna. This is their first new album since 2016's Hardwired...To Self-Destruct.